2003
DOI: 10.1002/app.12859
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic oscillations effect on rheological and processing properties of metallocene‐catalyzed linear low density polyethylene

Abstract: ABSTRACT:The effects of ultrasonic oscillations and die materials on die pressure, productivity of extrusion, melt viscosity of metallocene-catalyzed linear low density polyethylene (mLLDPE), as well as their mechanism were studied in a special ultrasonic oscillations extrusion system developed in our lab. Die materials used in our experiment included steel, brass, and polytetrafluoroethylene (PTFE) . The experimental results showed that ultrasonic oscillations as well as die materials have great influence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…23 The maximum power output and fixed frequency of the generator were 300 W and 20 kHz. The POE was mixed with MAH, DCP, and St which were dissolved in acetone before extrusion.…”
Section: Samples Preparationmentioning
confidence: 99%
“…23 The maximum power output and fixed frequency of the generator were 300 W and 20 kHz. The POE was mixed with MAH, DCP, and St which were dissolved in acetone before extrusion.…”
Section: Samples Preparationmentioning
confidence: 99%
“…If we oscillated the nozzle up and down, the diameter of the strand slightly increased. This is because the viscosity of the PCL solution decreased due to the oscillation of the nozzle [22][23][24]. The vibration force applied to the polymer solution reduced the van der Waals force connecting the macromolecules of the polymer solution, so that the viscous force between the macromolecules decreased.…”
Section: Resultsmentioning
confidence: 95%
“…Our main experiment is a specially designed ultrasound‐assisted extrusion system developed in our lab [28]. The die, which is constructed by steel, includes a special horn serving as a capillary, whose length/diameter ( L / D ) ratio is fixed at 8.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, ultrasound technology has been developed to improve the processing properties of polymers during the extrusion [19–23]. In our laboratory, different kinds of polyethylene melts such as HDPE, LLDPE, and metallocene‐catalyzed linear low‐density polyethylene (mLLDPE), have been studied during ultrasound‐assisted extrusion [24–28]. It was found that the die pressure and apparent viscosity of polyethylene melts in the extrusion were greatly decreased with increasing ultrasound power.…”
Section: Introductionmentioning
confidence: 99%